PERANCANGAN TRAFFIC SPIKES OTOMATIS TYPE SURFACED MOUNTED BERBASIS MICROCONTROLLER ARDUINO UNO DAN SENSOR ID CARD - Sudirman Lubis; Edi Sarman Hasibuan (Akademi Komunitas Negeri Aceh Barat, 2020)
Abstract Traffic Spikes are devices or devices used to obstruct or stop the movement of wheeled vehicles by piercing vehicle tires. In this study to meet the requirements for traffic spikes, an arduino uno microcontroler-based automatic traffic spikes control system with identity card (ID Card) sensor was designed. In its design, a Surface-Mounted Traffic Spikes has 8 blades which are used to pierce the tires of the vehicle if the user does not carry out the procedures of using traffic spikes correctly, then the automatic control system reads the tool, the blade stands upright with the position 900 and given a load for testing in the form of a car, and the blade is able to withstand the load as desired, then the tool has been successfully tested. The design of the resulting traffic spikes has dimensions of length of 1000 mm, width of 610 mm, and height of 100 mm. The results of the traffic spikes components are frame design, frame cover design, shaft design, spikes blade design, pillow block design, peg design. The simulation results of the design made are the displacement process has a minimum load consisting of 1000e - 030 mm and an acceptable maximum load of 3,954e - 000 mm, stress has an acceptable minimum load of 1,005e + 003 Nm ¬-2 and pressure the maximum acceptable is 3,411e - 009 and the maximum load is 9.278e-004. . Keywords: Traffic Spikes, Microcontroller Arduino Uno, ID Cards __________________________ Abstrak Traffic Spikes adalah perangkat atau alat yang digunakan untuk menghalangi atau menghentikan pergerakan kendaraan roda dengan menusuk ban kendaraan. Dalam penelitian kali ini untuk memenuhi syarat traffic spikes, maka dirancang sistem kendali otomatis traffic spikes berbasis microcontroler arduino uno dengan sensor identity card (ID Card). Dalam perancangannya dibuat sebuah traffic spikes dalam bentuk tanjakan (Surface-Mounted Traffic Spikes) yang memiliki 8 buah pisau yang digunakan untuk menusuk ban kendaraan apabila pengguna tidak menjalankan prosedur pemakaian traffic spikes dengan benar maka alat membaca sistem kendali otomatis, mata pisau berdiri tegak dengan posisi 900 dan diberi beban untuk pengujian yang berupa mobil, dan mata pisau mampu menahan beban seperti yang diinginkan, maka alat dinyatakan telah berhasil pengujiannya. Perancangan traffic spikes yang dihasilkan memiliki dimensi panjang 1000 mm, lebar 610 mm, dan tinggi 100 mm. Hasil rancangan komponen-komponen traffic spikes rancangan rangka, rancang penutup rangka, rancangan poros, rancangan pisau spikes, rancangan pillow block, rancangan pasak. Hasil Simulasi dari rancangan yang dibuat adalah proses dibuat displacement memiliki beban minimal yang terdiri sebesar 1000e – 030 mm dan bebanmaksimal yang dapat diterima sebesar 3.954e – 000 mm, stress memiliki beban minimal yang dapat diterima sebesar 1.005e + 003 N.m¬-2 dan tekanan maksimal yang dapat diterima sebesar 3.411e – 009 dan beban maksimalnya 9.278e-004. Kata Kunci: Traffic Spikes, Microcontroller Arduino Uno, ID Card __________________________